Understanding how patients with psychosis would prefer to be contacted about research. Issue 1 (2nd January 2021) - Mbanu, Jennifer
ABSTRACT: Background: There has been no published research exploring the attitudes of people with psychosis to different communication methods for being contacted about research. Methods: Fifty patients diagnosed with schizophrenia, psychosis and related disorders completed an open ended questionnaire about: The method(s) by which patients with psychosis would prefer to be contacted about research opportunities; attitudes towards texting as a proposed method for informing patients about research studies; attitudes towards being contacted from a private number; and preferred contact method(s) for research appointment reminders. Results: Emergent themes from the questionnaire are presented. Conclusions: The implications for improving research engagement within the psychosis population are discussed and scope for further research highlighted.